Analisis Motivasi Belajar Matematika Siswa Kelas XI IPA pada Masa Pandemi Covid-19 - Nurhayati, Firastika Eka; Purwanto, Sigid Edy (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2021)
Motivation is an element that is owned by every individual, especially in the learning process, because motivation acts as a driving force for an activity that has a purpose. The outbreak of corona virus 19 caused the teaching and learning process to be carried out remotely, causing the learning process to be uncontrolled by the teacher. This study aims to analyze students' motivation to learn mathematics during the Covid-19 pandemic. This research was conducted in one of the private high schools in East Jakarta, Pasar Rebo District. The data were collected using a learning motivation questionnaire sheet consisting of 26 statements and interviews which consisted of 11 questions involving the math teacher as the resource. The questionnaire analysis technique was analyzed using descriptive statistics, while the interview sheets were analyzed qualitatively. The research sample was 43 students of class XI IPA. The results of the research and interviews showed that the students' motivation to learn mathematics in class XI IPA was 2.98 with a good category. The conclusion of this study is that students of class XI IPA have good motivation in learning mathematics during the Covid-19 epidemic.